A highly flame-retardant industrial equipment cable with excellent dynamic durability and a preparation method thereof

By using high-purity oxygen-free copper conductor layer, shielding layer in tin-plated copper braided mesh, insulating layer fillers for modified nanoparticles and sericite powder, as well as flame retardants for aluminum hydroxide and zinc borate in high flame retardant industrial equipment cables, the degradation and aging problems of traditional high flame retardant cables are solved, and excellent dynamic durability and high flame retardant performance are achieved.

CN119541937BActive Publication Date: 2025-04-08HANGZHOU LINAN GUANGDA CABLE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510088202.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-08
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

After adding flame retardant additives to traditional high-fire retardant cables, the electrical insulation and mechanical properties are degraded, and they are prone to aging and breaking in complex environments, and may release toxic gases.

Method used

The insulating layer material is mainly composed of high-purity oxygen-free copper conductor layer, tin-plated copper braided mesh shielding layer, and polyetherimide as the insulating layer material, and a combined filler of modified nanoparticles and sericite powder, as well as flame retardants of aluminum hydroxide and zinc borate, and an insulating layer and an outer protective layer are formed through a twin-screw extruder.

Benefits of technology

While achieving high flame retardant performance, it maintains good moisture resistance, heat resistance, corrosion resistance and aging resistance, greatly improving the application durability and service life of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the field of equipment cables, and in particular to a highly flame-retardant industrial equipment cable with excellent dynamic durability and a preparation method thereof. The highly flame-retardant industrial equipment cable with excellent dynamic durability has a structure including a conductor layer located in the center, an inner shielding layer wrapped outward layer by layer, an insulating layer, and an outer protective layer. The equipment cable prepared by the present application not only has excellent flame retardant properties, but also can maintain good moisture resistance, heat stability, corrosion resistance, and aging resistance at the same time, greatly enhancing its application durability, having very excellent application quality and service life, meeting the diverse functional requirements of modern industrial equipment for equipment cables, and having broad application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of equipment cables, and in particular to a highly flame-retardant industrial equipment cable with excellent dynamic durability and a preparation method thereof. Background Art

[0002] In modern industrial environments, industrial equipment cables are key components for power transmission and signal communication, and their performance is directly related to the stability and safety of the entire system. Especially under harsh working conditions such as high temperature, high humidity, chemical corrosion, and frequent changes in mechanical stress, cables must not only have excellent electrical performance, but also excellent dynamic durability to ensure long-term reliable operation. In recent years, with the improvement of industrial automation levels and the enhancement of fire safety awareness, the market demand for highly flame-retardant industrial equipment cables has been growing.

[0003] Traditional industrial equipment cables are usually composed of conductors, insulation layers and sheaths, among which the selection of insulation layer materials and sheath materials is crucial to the overall performance of the cable. In order to meet different application requirements, cable manufacturers are constantly exploring new materials and technologies, such as adding flame retardants or using special polymers to improve the insulation and flame retardant properties of cables. In addition, by improving the production process, such as using a twin-screw extruder for melt extrusion granulation, insulation layers and cable sheaths with more uniform structures and better physical properties can be manufactured.

[0004] However, although the existing technology has made certain progress, there are still some problems that need to be solved. On the one hand, the traditional high flame retardant cables often have a large amount of flame retardant additives added, which leads to a decrease in electrical insulation and mechanical properties, and these additives may release toxic gases during the combustion process; on the other hand, due to insufficient mechanical strength, they are prone to aging and breakage when subjected to dynamic loads such as bending and stretching for a long time, especially in complex environmental areas, high humidity, high temperature and strong light environments will significantly affect the quality and service life of the cable.

[0005] Therefore, in order to effectively solve the above problems, the present application provides a highly flame-retardant industrial equipment cable with excellent dynamic durability and a preparation method thereof. The equipment cable prepared in the present application not only has excellent flame retardant properties, but also can maintain good moisture resistance, heat stability, corrosion resistance and aging resistance. The performance, which greatly enhances its application durability, has very excellent application quality and service life, meets the diverse functional requirements of modern industrial equipment for equipment cables, and has broad application potential. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides a highly flame-retardant industrial equipment cable with excellent dynamic durability, whose structure includes a conductor layer located in the center, an inner shielding layer, an insulating layer and an outer protective layer wrapped outward layer by layer.

[0007] As a preferred solution, the conductor layer is any one of high-purity oxygen-free copper, silver-plated copper wire, aluminum alloy, tin-plated copper wire and copper-clad aluminum.

[0008] As a preferred solution, the conductor layer is high-purity oxygen-free copper.

[0009] As a preferred solution, the thickness of the conductor layer is 0.3-0.8 mm.

[0010] As a preferred solution, the inner shielding layer is at least one of a tinned copper braided mesh, a silver-plated copper braided mesh, an aluminum foil, a composite metal tape and a stainless steel braided mesh.

[0011] As a preferred solution, the inner shielding layer is a tinned copper braided mesh.

[0012] As a preferred solution, the thickness of the inner shielding layer is 0.1-0.4 mm.

[0013] As a preferred solution, the insulating layer comprises, by weight, 40 to 60 parts of polyetherimide, 5 to 10 parts of toughening agent, 1 to 2 parts of antioxidant, 0.5 to 1.5 parts of ultraviolet absorber, 1 to 3 parts of lubricant, 10 to 20 parts of filler, and 1 to 6 parts of flame retardant.

[0014] As a preferred solution, the mass ratio of the polyetherimide, toughening agent and filler is (45-55): (6-8): (14-18).

[0015] As a preferred solution, the mass ratio of the polyetherimide, toughening agent and filler is (48-52): (7-8): (15-17).

[0016] As a preferred solution, the mass ratio of the filler to the flame retardant is (14-18): (2-4).

[0017] As a preferred solution, the mass ratio of the filler to the flame retardant is (15-17): (2.5-3).

[0018] As a preferred solution, the oxygen index of the polyetherimide is 30-40%.

[0019] As a preferred solution, the antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate or trisnonylphenyl phosphite.

[0020] As a preferred solution, the ultraviolet absorber is 2-hydroxy-4-n-octyloxybenzophenone or 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole.

[0021] As a preferred solution, the lubricant is polypropylene wax or fluoroalkyl silane.

[0022] As a preferred solution, the lubricant is polypropylene wax.

[0023] As a preferred solution, the filler is a composition of modified nanoparticles and sericite powder.

[0024] As a preferred solution, the mass ratio of the modified nanoparticles to the sericite powder is (1.2-1.6): (3-3.5).

[0025] As a preferred scheme, the preparation method of the modified nanoparticles specifically includes the following steps: S1: mixing silicon dioxide and aluminum chloride and adding them to a DMF (N,N-Dimethylformamide) solution, then adding succinic anhydride and heating to 60-65°C and keeping warm for 2-3 hours; S2: then adding tetraethyl orthosilicate, mixing and stirring evenly, then adding terephthalic acid, 4,4'-biphenyldicarboxylic acid and isophthalic acid, and adding hydrochloric acid to adjust the pH to 5.5-6; S3: heating to 110-120°C, keeping warm for reaction for 16-20 hours, naturally cooling to room temperature after the reaction is completed, adding ammonia water to adjust the pH to 7-7.5, rapidly stirring at 200-300rpm for 5-10 minutes, and then centrifuging to obtain a solid product, washing the solid product with ethanol and deionized water, and vacuum drying overnight to obtain the product.

[0026] As a preferred solution, the mass ratio of silicon dioxide, aluminum chloride and succinic anhydride is (0.4-0.5): (5-6): (0.6-0.8).

[0027] As a preferred solution, the mass ratio of aluminum chloride, tetraethyl orthosilicate, terephthalic acid, 4,4'-biphenyldicarboxylic acid and isophthalic acid is (5-6): (0.3-0.4): (2.2-2.6): (0.4-0.6): (0.05-0.1).

[0028] As a preferred solution, the average particle size of the silicon dioxide is 20-30 nm.

[0029] In the present application, by adding the above-mentioned modified nanoparticles, the modified nanoparticles and the sericite powder can be combined with each other in the insulation layer system to form a stepped system with layers interlaced with each other. The existence of this system can greatly increase the penetration resistance and penetration path length of water molecules and active molecules inside. At the same time, the silica particles on the surface of the framework structure of the modified nanoparticles guide the trace moisture inside and absorb it through the framework microporous structure, further removing the moisture in the internal system, making it impossible for moisture and active molecules with water molecules as carriers to be continuous with each other, and collide with each other to produce side reactions, thereby effectively improving the corrosion resistance, waterproofness and aging resistance of the equipment cable; on the other hand, its complex microporous structure can intercept oxygen at the combustion interface during flame retardant effect, block the rapid advancement of the combustion interface, and thus play an excellent auxiliary flame retardant effect.

[0030] As a preferred solution, the flame retardant is aluminum hydroxide, magnesium hydroxide, zinc borate, antimony oxide and basic magnesium carbonate.

[0031] As a preferred solution, the flame retardant is a combination of aluminum hydroxide and zinc borate.

[0032] As a preferred solution, the mass ratio of aluminum hydroxide to zinc borate is (3-4):(1.6-2).

[0033] As a preferred solution, the thickness of the insulating layer is 1.2-1.5 mm.

[0034] As a preferred solution, the outer protective layer is composed of the following raw materials, calculated by weight: 50-60 parts of thermoplastic polyurethane, 25-35 parts of glass fiber reinforcement, 2-4 parts of stabilizer, and 1-3 parts of impact resister.

[0035] As a preferred solution, the mass ratio of the thermoplastic polyurethane to the glass fiber reinforcement is (52-60): (28-33).

[0036] As a preferred solution, the mass ratio of the thermoplastic polyurethane to the glass fiber reinforcement is 58:30.

[0037] As a preferred solution, the fiber reinforcement material is glass fiber reinforced plastic.

[0038] As a preferred solution, the glass fiber content in the glass fiber reinforced plastic is 20-35wt%.

[0039] As a preferred solution, the stabilizer is at least one of organic tin stabilizers.

[0040] As a preferred solution, the stabilizer is di-n-octyltin maleate.

[0041] As a preferred solution, the impact-resistant agent is maleic anhydride grafted polyethylene.

[0042] As a preferred solution, the thickness of the outer protective layer is 1.5~2 mm.

[0043] The second aspect of the present application provides a method for preparing the above-mentioned highly flame-retardant industrial equipment cable with excellent dynamic durability, which specifically includes the following steps: S1: preparing conductor layer raw material filaments, twisting them into conductor wires after annealing treatment to obtain a conductor layer; S2: using an automatic braiding machine to weave the inner shielding layer into a mesh structure, covering the outside of the conductor layer, ensuring that the braiding density is uniform and there are no obvious gaps; S3: placing the insulating layer material into a twin-screw extruder, melt-extrude it in the temperature range of 180~220°C, and calendering to form an insulating layer of corresponding thickness and wrap the inner shielding layer; S4: also using a twin-screw extruder to heat the outer protective sheath material with a good ratio to 200~220°C, and then extrude it through a mold to form an outer protective layer of corresponding thickness, completely covering the insulating layer, and obtaining it.

[0044] The beneficial effects of this application are:

[0045] 1. The present application provides a highly flame-retardant industrial equipment cable with excellent dynamic durability, which not only has excellent flame-retardant properties, but also can maintain good moisture resistance, heat stability, corrosion resistance and aging resistance, etc., greatly enhancing its application durability, and has very excellent application quality and service life, meeting the diverse functional requirements of modern industrial equipment for equipment cables, and has broad application potential.

[0046] 2. The present application provides a highly flame-retardant industrial equipment cable with excellent dynamic durability. With the addition of modified nanoparticles, the modified nanoparticles can be combined with sericite powder to form a stepped system that interpenetrates each other layer by layer in the insulation layer system. The existence of this system can greatly increase the penetration resistance and penetration path length of water molecules and active molecules inside. At the same time, the trace amount of water inside is guided by the silica particles on the surface of the framework structure of the modified nanoparticles, and absorbed by the microporous structure of the framework, further removing the water in the internal system, so that the water and the active molecules with water molecules as carriers cannot be continuous with each other, and collide with each other to produce side reactions, thereby effectively improving the corrosion resistance, waterproofness and aging resistance of the equipment cable.

[0047] 3. The present application provides a highly flame-retardant industrial equipment cable with excellent dynamic durability. The addition of modified nanoparticles and their complex microporous structure can intercept oxygen at the combustion interface during the flame retardant effect, blocking the rapid advancement of the combustion interface, thereby playing an excellent auxiliary flame retardant effect. DETAILED DESCRIPTION

[0048] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0049] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0050] Example 1

[0051] Embodiment 1 provides a highly flame-retardant industrial equipment cable with excellent dynamic durability, the structure of which includes a conductor layer located in the center, an inner shielding layer, an insulating layer and an outer protective layer wrapped outward layer by layer.

[0052] The thickness of the conductor layer is 0.5 mm, and the conductor layer is high-purity oxygen-free copper purchased from Shandong Fengshen Metal Products Co., Ltd., China.

[0053] The inner shielding layer is tinned copper braided mesh with a thickness of 0.3mm.

[0054] The raw materials of the insulating layer, calculated by weight, are: 51.6 parts of polyetherimide, 7.2 parts of toughening agent, 1.2 parts of antioxidant, 0.7 parts of ultraviolet absorber, 2.1 parts of lubricant, 16.1 parts of filler and 2.8 parts of flame retardant.

[0055] The polyetherimide had an oxygen index of 38% and was purchased from SABIC as ULTEM™ 1010.

[0056] The antioxidant was Irganox 1076, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate; the UV absorber was 2-hydroxy-4-n-octyloxybenzophenone; and the lubricant was polypropylene wax, purchased from Shanghai Hongzhuang Chemical Technology Co., Ltd., China, selling a CS-52NC model product.

[0057] The filler is a composite of modified nanoparticles and sericite powder, and the mass ratio of the two is 1.5:3.3.

[0058] The preparation method of modified nanoparticles specifically includes the following steps, calculated by mass: S1: 0.42 parts of silicon dioxide and 5.6 parts of aluminum chloride are mixed and added to 160 parts of DMF solution, and then 0.7 parts of succinic anhydride are added and the temperature is raised to 65°C and kept warm for 3 hours; S2: 0.34 parts of ethyl orthosilicate are added, and after mixing and stirring evenly, 2.4 parts of terephthalic acid, 0.5 parts of 4,4'-biphenyldicarboxylic acid and 0.08 parts of isophthalic acid are added, and hydrochloric acid is added to adjust the pH to 6; S3: the temperature is raised to 120°C, and the temperature is kept for reaction for 19 hours. After the reaction is completed, the temperature naturally drops to room temperature, and ammonia water is added to adjust the pH to 7.5. After rapid stirring at 200rpm for 8 minutes, the solid product is obtained by centrifugation and filtration. The solid product is washed with ethanol and deionized water, and vacuum dried overnight.

[0059] The average particle size of silica was 24 nm.

[0060] The flame retardant is a composition of aluminum hydroxide and zinc borate, and the mass ratio of the two is 3.4:1.8.

[0061] The thickness of the insulation layer is 1.4 mm.

[0062] The outer protective layer is composed of 58 parts of thermoplastic polyurethane, 30 parts of glass fiber reinforcement, 2.4 parts of stabilizer and 1.8 parts of impact resistant agent, calculated by weight.

[0063] Thermoplastic polyurethane was purchased from BASF in Germany as Elastollan® C 980A.

[0064] The fiber reinforcement material is glass fiber reinforced plastic; the glass fiber content in the glass fiber reinforced plastic is 30wt%, and the product is a VX4930 PBT (Polybutylene Terephthalate) product purchased from Saudi Basic Industries Corporation.

[0065] The stabilizer is di-n-octyltin maleate; the impact agent is maleic anhydride grafted polyethylene, a ZJ-800E model product sold by Wuhan Huaxiang Kejie Biotechnology Co., Ltd., China.

[0066] The thickness of the outer protective layer is 1.8 mm.

[0067] The second aspect of the present embodiment provides a method for preparing the above-mentioned highly flame-retardant industrial equipment cable with excellent dynamic durability, which specifically includes the following steps: S1: preparing conductor layer raw material filaments, twisting them into conductor wires after annealing treatment to obtain a conductor layer; S2: using an automatic braiding machine to weave the inner shielding layer into a mesh structure, covering the outside of the conductor layer, ensuring that the braiding density is uniform and there are no obvious gaps; S3: placing the insulating layer material into a twin-screw extruder, melt-extrude it in the temperature range of 190~200°C, and calendering to form an insulating layer of corresponding thickness and wrap the inner shielding layer; S4: also using a twin-screw extruder to heat the outer protective sheath material with a good ratio to 210°C, and then extrude it through a mold to form an outer protective layer of corresponding thickness, completely covering the insulating layer, and obtaining it.

[0068] Example 2

[0069] Embodiment 2 provides a highly flame-retardant industrial equipment cable with excellent dynamic durability, the structure of which includes a conductor layer located in the center, an inner shielding layer, an insulating layer and an outer protective layer wrapped outward layer by layer.

[0070] The thickness of the conductor layer is 0.5 mm, and the conductor layer is high-purity oxygen-free copper purchased from Shandong Fengshen Metal Products Co., Ltd., China.

[0071] The inner shielding layer is tinned copper braided mesh with a thickness of 0.3mm.

[0072] The raw materials of the insulating layer, calculated by weight, are: 45.8 parts of polyetherimide, 6.1 parts of toughening agent, 1.2 parts of antioxidant, 0.7 parts of ultraviolet absorber, 2.1 parts of lubricant, 14.5 parts of filler and 2.1 parts of flame retardant.

[0073] The polyetherimide had an oxygen index of 38% and was purchased from SABIC as ULTEM™ 1010.

[0074] The antioxidant was Irganox 1076, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate; the UV absorber was 2-hydroxy-4-n-octyloxybenzophenone; and the lubricant was polypropylene wax, purchased from Shanghai Hongzhuang Chemical Technology Co., Ltd., China, selling a CS-52NC model product.

[0075] The filler is a composite of modified nanoparticles and sericite powder, and the mass ratio of the two is 1.5:3.3.

[0076] The preparation method of modified nanoparticles specifically includes the following steps, calculated by mass: S1: 0.42 parts of silicon dioxide and 5.6 parts of aluminum chloride are mixed and added to 160 parts of DMF solution, and then 0.7 parts of succinic anhydride are added and the temperature is raised to 65°C and kept warm for 3 hours; S2: 0.34 parts of ethyl orthosilicate are added, and after mixing and stirring evenly, 2.4 parts of terephthalic acid, 0.5 parts of 4,4'-biphenyldicarboxylic acid and 0.08 parts of isophthalic acid are added, and hydrochloric acid is added to adjust the pH to 6; S3: the temperature is raised to 120°C, and the temperature is kept for reaction for 19 hours. After the reaction is completed, the temperature naturally drops to room temperature, and ammonia water is added to adjust the pH to 7.5. After rapid stirring at 200rpm for 8 minutes, the solid product is obtained by centrifugation and filtration. The solid product is washed with ethanol and deionized water, and vacuum dried overnight.

[0077] The average particle size of silica was 24 nm.

[0078] The flame retardant is a composition of aluminum hydroxide and zinc borate, and the mass ratio of the two is 3.4:1.8.

[0079] The thickness of the insulation layer is 1.4 mm.

[0080] The outer protective layer is composed of 60 parts of thermoplastic polyurethane, 28 parts of glass fiber reinforcement, 2.4 parts of stabilizer and 1.8 parts of impact resistant agent, calculated by weight.

[0081] Thermoplastic polyurethane was purchased from BASF in Germany as Elastollan® C 980A.

[0082] The fiber reinforcement material is glass fiber reinforced plastic; the glass fiber content in the glass fiber reinforced plastic is 30wt%, and the PBT product of model VX4930 is purchased from Saudi Basic Industries Corporation.

[0083] The stabilizer is di-n-octyltin maleate; the impact agent is maleic anhydride grafted polyethylene, a ZJ-800E model product sold by Wuhan Huaxiang Kejie Biotechnology Co., Ltd., China.

[0084] The thickness of the outer protective layer is 1.8 mm.

[0085] The second aspect of the present embodiment provides a method for preparing the above-mentioned highly flame-retardant industrial equipment cable with excellent dynamic durability, which specifically includes the following steps: S1: preparing conductor layer raw material filaments, twisting them into conductor wires after annealing treatment to obtain a conductor layer; S2: using an automatic braiding machine to weave the inner shielding layer into a mesh structure, covering the outside of the conductor layer, ensuring that the braiding density is uniform and there are no obvious gaps; S3: placing the insulating layer material into a twin-screw extruder, melt-extrude it in the temperature range of 190~200°C, and calendering to form an insulating layer of corresponding thickness and wrap the inner shielding layer; S4: also using a twin-screw extruder to heat the outer protective sheath material with a good ratio to 210°C, and then extrude it through a mold to form an outer protective layer of corresponding thickness, completely covering the insulating layer, and obtaining it.

[0086] Comparative Example 1

[0087] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the raw materials of the insulating layer, by mass, are: 65.5 parts of polyetherimide, 6.1 parts of toughening agent, 1.2 parts of antioxidant, 0.7 parts of ultraviolet absorber, 2.1 parts of lubricant, 5.5 parts of filler, and 2.1 parts of flame retardant.

[0088] Comparative Example 2

[0089] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the raw materials of the insulating layer, by mass, are: 45.8 parts of polyetherimide, 6.5 parts of toughening agent, 1.2 parts of antioxidant, 0.7 parts of ultraviolet absorber, 2.1 parts of lubricant, 25.5 parts of filler, and 2.1 parts of flame retardant.

[0090] Comparative Example 3

[0091] The specific implementation of this comparative example is basically the same as that of Example 1, except that the filler is a composition of modified nanoparticles and sericite powder, and the mass ratio of the two is 0.5:4.8.

[0092] Comparative Example 4

[0093] The specific implementation of this comparative example is basically the same as that of Example 1, except that the filler is a composition of modified nanoparticles and sericite powder, and the mass ratio of the two is 2.5:1.

[0094] Comparative Example 5

[0095] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified nanoparticles specifically includes the following steps, calculated by mass: S1: 1.2 parts of silicon dioxide and 3.2 parts of aluminum chloride are mixed and added to 160 parts of DMF solution, and then 0.7 parts of succinic anhydride are added and the temperature is raised to 65°C and kept warm for 3 hours; S2: 0.34 parts of ethyl orthosilicate are added, and after mixing and stirring evenly, 2.4 parts of terephthalic acid, 0.5 parts of 4,4'-biphenyldicarboxylic acid and 0.08 parts of isophthalic acid are added, and hydrochloric acid is added to adjust the pH to 6; S3: the temperature is raised to 120°C, and the temperature is kept for reaction for 19 hours. After the reaction is completed, the temperature is naturally lowered to room temperature, and ammonia water is added to adjust the pH to 7.5. After rapid stirring at 200rpm for 8 minutes, the solid product is obtained by centrifugation and filtration. The solid product is washed with ethanol and deionized water, and vacuum dried overnight.

[0096] The average particle size of silica was 45 nm.

[0097] Comparative Example 6

[0098] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified nanoparticles specifically includes the following steps, calculated by mass: S1: 0.22 parts of silicon dioxide and 8.5 parts of aluminum chloride are mixed and added to 160 parts of DMF solution, and then 0.7 parts of succinic anhydride are added and the temperature is raised to 65°C and kept warm for 3 hours; S2: 0.34 parts of tetraethyl orthosilicate are added, and after mixing and stirring evenly, 6.5 parts of terephthalic acid and 0.2 parts of 4,4'-biphenyldicarboxylic acid are added, and hydrochloric acid is added to adjust the pH to 6; S3: the temperature is raised to 120°C, and the reaction is kept warm for 19 hours. After the reaction is completed, the temperature naturally drops to room temperature, and ammonia water is added to adjust the pH to 7.5. After rapid stirring at 200rpm for 8 minutes, the solid product is obtained by centrifugation and filtration. The solid product is washed with ethanol and deionized water, and vacuum dried overnight.

[0099] The average particle size of silica was 40 nm.

[0100] Performance Evaluation

[0101] Insulation test: The insulating layer prepared in the embodiment and the comparative example was tested, and the volume resistivity of the insulating layer was detected under a 25° C. The test value was the average value of 10 tests and recorded in Table 1.

[0102] Mechanical property test: The insulating layers prepared in the embodiments and comparative examples were tested for tensile strength and elongation at break using a universal material testing machine. The test values ​​were averaged over 10 tests and recorded in Table 1.

[0103] Flame retardancy test: The cables prepared in the examples and comparative examples were tested according to the reference standard GB / T 18380.31-2008. The test length was 3 m. The remaining cable length at the end of the test was recorded. The test value was the average value of 10 tests and recorded in Table 2.

[0104] Waterproof test: The insulating layer prepared in the embodiment and the comparative example was tested, and the moisture permeability resistance test was performed with reference to GB / T 1037-2021. The test value was the average value of 10 tests and recorded in Table 2.

[0105] Corrosion resistance test: The insulating layer prepared in the embodiment and the comparative example was tested. The test environment temperature was 40±2°C, the humidity was 95±2%, the test solution was 5wt% NaCl solution, the spraying rate was 2mL / 16h·80cm², and the salt spray corrosion resistance test time was 2400h. After the test, observe whether there is corrosion damage, yellowing, cracking or blistering. If there is, it is recorded as unqualified, otherwise it is qualified. 50 groups of samples were tested in each group, and the qualified rate results are recorded in Table 1.

[0106] Table 1 Performance test results 1

[0107]

[0108] Table 2 Performance test results 2

[0109]

[0110] It can be seen from the data results of the embodiments and comparative examples of the present application and Tables 1 and 2 that embodiments 1 and 2 of the present application have obvious advantages over comparative examples 1 to 6 in terms of mechanical properties, waterproof properties, flame retardant properties, insulation properties and corrosion resistance. This is mainly due to the combined effect of the modified functional particles added as specified in the present application and other matching schemes. Comparative examples 1 to 6 did not fully adopt the technical scheme specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests, which further proves the necessity of the technical scheme specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. A highly flame-retardant industrial equipment cable with excellent dynamic durability, characterized by: The structure includes a conductor layer in the center, an inner shielding layer, an insulating layer and an outer protective layer wrapped outwards layer by layer; The thickness of the conductor layer is 0.3-0.8 mm; The inner shielding layer is at least one of a tinned copper braided mesh, a silver-plated copper braided mesh, an aluminum foil, a composite metal tape, and a stainless steel braided mesh; The thickness of the inner shielding layer is 0.1-0.4 mm; The insulating layer comprises, by weight, 40 to 60 parts of polyetherimide, 5 to 10 parts of toughening agent, 1 to 2 parts of antioxidant, 0.5 to 1.5 parts of ultraviolet absorber, 1 to 3 parts of lubricant, 10 to 20 parts of filler and 1 to 6 parts of flame retardant. The oxygen index of the polyetherimide is 30-40%; The antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate or trisnonylphenyl phosphite; The filler is a composition of modified nanoparticles and sericite powder; the mass ratio of the modified nanoparticles to the sericite powder is (1.2-1.6): (3-3.5); The preparation method of the modified nanoparticles specifically comprises the following steps: S1: adding silicon dioxide and aluminum chloride to a DMF solution, then adding succinic anhydride and heating to 60-65°C for 2-3 hours; S2: then adding ethyl orthosilicate, mixing and stirring evenly, then adding terephthalic acid, 4,4'-biphenyldicarboxylic acid and isophthalic acid, and adding hydrochloric acid to adjust the pH to 5.5-6; S3: heating to 110-120°C, keeping the temperature for reaction for 16-20 hours, naturally cooling to room temperature after the reaction is completed, adding ammonia water to adjust the pH to 7-7.5, rapidly stirring at 200-300 rpm for 5-10 minutes, and then centrifuging to obtain a solid product, washing the solid product with ethanol and deionized water, and vacuum drying overnight to obtain the product.

2. The highly flame-retardant industrial equipment cable with excellent dynamic durability according to claim 1, characterized in that: The mass ratio of the polyetherimide, toughening agent and filler is (45-55): (6-8): (14-18).

3. The highly flame-retardant industrial equipment cable with excellent dynamic durability according to claim 2, characterized in that: The mass ratio of the filler to the flame retardant is (14-18): (2-4).

4. The highly flame-retardant industrial equipment cable with excellent dynamic durability according to claim 3, characterized in that: The conductor layer is any one of high-purity oxygen-free copper, silver-plated copper wire, aluminum alloy, tin-plated copper wire and copper-clad aluminum.

5. The highly flame-retardant industrial equipment cable with excellent dynamic durability according to claim 4, characterized in that: The ultraviolet absorber is 2-hydroxy-4-n-octyloxybenzophenone or 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole.

6. The highly flame-retardant industrial equipment cable with excellent dynamic durability according to claim 5, characterized in that: The mass ratio of silicon dioxide, aluminum chloride and succinic anhydride is (0.4-0.5): (5-6): (0.6-0.8).

7. The highly flame-retardant industrial equipment cable with excellent dynamic durability according to claim 6, characterized in that: The mass ratio of the aluminum chloride, tetraethyl orthosilicate, terephthalic acid, 4,4'-biphenyldicarboxylic acid and isophthalic acid is (5-6): (0.3-0.4): (2.2-2.6): (0.4-0.6): (0.05-0.1).

8. The highly flame-retardant industrial equipment cable with excellent dynamic durability according to claim 7, characterized in that: The average particle size of the silicon dioxide is 20-30 nm.

9. The highly flame-retardant industrial equipment cable with excellent dynamic durability according to claim 8, characterized in that: The outer protective layer is made of the following raw materials, calculated by weight: 50-60 parts of thermoplastic polyurethane, 25-35 parts of glass fiber reinforcement, 2-4 parts of stabilizer, and 1-3 parts of impact resistance agent; The fiber reinforcement material is glass fiber reinforced plastic; the glass fiber content in the glass fiber reinforced plastic is 20-35wt%.

10. A method for preparing a highly flame-retardant industrial equipment cable with excellent dynamic durability according to any one of claims 1 to 9, characterized in that: The specific steps include: S1: Prepare the conductor layer raw material filaments, anneal them and twist them into conductor wires to obtain the conductor layer; S2: Use an automatic braiding machine to weave the inner shielding layer into a mesh structure, covering the outside of the conductor layer, ensuring that the braiding density is uniform and there are no obvious gaps; S3: Put the insulating layer material into a twin-screw extruder, melt-extrude it in the temperature range of 180~220°C, and calender it to form an insulating layer of corresponding thickness and wrap the inner shielding layer; S4: Also use a twin-screw extruder to heat the outer protective cover material with a good ratio to 200~220℃, and then extrude it through a mold to form an outer protective layer of corresponding thickness, completely covering the insulating layer, and you have it.

Citation Information

Patent Citations

  • Cable and production method thereof

    CN112466533A

  • Copolyamide hot melt adhesive and preparation method thereof

    CN119119951A